(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: The current study was designed to describe roles of oxidative stress via the measurementof malondialdehyde and total antioxidant markers, and apoptosis through the measurement of caspase 3marker, as mechanisms of liver toxicity induced by irinotecan; and to explore the possible protective effectsof high- and low- doses of lutein against irinotecan induced toxicity in the liver of rats.Methods: Thirty six (36) Sprague-Dawley rats were randomly divided into six groups: Groups ?, ratsreceived single oral daily dose of dimethyl sulfoxide (4 ml/kg); Group ?? (irinotecan-treated), receivedsingle oral daily dose of dimethyl sulfoxide (4ml/kg) for 25 days by oral gavage and subsequently receivedirinotecan (50mg/kg) on days: 5, 10, 15 (total dose=150 mg/kg) by intraperitoneal injection; Groups ???and ?V, received oral dose of lutein (6mg/kg/day) and (24mg/kg/day), respectively by oral gavage for 25successive days (lutein-treated); Groups V and V? (lutein+ irinotecan), received oral dose of lutein (6mg/kg/day) and (24mg /kg/day), respectively by oral gavage for 25 successive days, and subsequently receivedirinotecan (50mg /kg body weight) on days: 5, 10, 15 (total dose=150 mg/kg) by intraperitoneal injection.Results: Orally-administered lutein with total cumulative dose of irinotecan (Groups V and VI), resultedin significant reduction (P<0.05) of serum aspartate aminotransferase and alanine aminotransferase, andsignificant reduction (P<0.05) of malondialdehyde; but, significant elevation (P<0.05) of serum totalantioxidant capacity; and there was significant reduction in caspase 3in liver tissues homogenates comparedto the corresponding levels in the group of rats administered irinotecan (Group II).Conclusion: Results of the current finding suggested that administration of lutein may be a useful compoundthat alleviated irinotecan induced toxicity to the liver